Acyclic nucleoside phosphonates: a study on cytochrome P450 gene expression. (5th March 2014) - Nekvindova, Jana; Contreras, Juan Antonio; Juvan, Peter; Fon Tacer, Klementina; Anzenbacher, Pavel; Zidek, Zdenek; Kopecna Zapletalova, Michaela; Rozman, Damjana; Anzenbacherova, Eva
Abstract: 1. Nucleotide analogues comprise an important class of drugs used in treatment of viral infections but also cancer. These drugs affect the structural integrity of DNA and activate different pathways and processes in the cell and may directly or indirectly influence the drug metabolizing system. Adefovir dipivoxil (AD) and tenofovir disoproxil (TD) are nucleotide analogues approved for the treatment of chronic hepatitis B and/or HIV/AIDS infection. 2. To evaluate the risk of their drug–drug interactions on the level of drug metabolism, an effect of both compounds on cytochromes P450 expression was studied using cDNA microarrays, real-time RT-PCR and immunoblotting. Mice were given intraperitoneally 25 mg/kg of AD or TD, respectively. As a positive control, a combination of prototypic cytochromes P450 (CYP) inducers, phenobarbital and β-naphthoflavone was chosen. 3. The data obtained showed a significant CYP induction in the positive control group, but no clinically significant induction of CYP genes by AD or TD was observed. Our results support the evidence of safety of AD and TD with respect to drug–drug interactions based on enzyme induction. These findings are important as a plethora of new antivirals of different types are being tested and introduced to clinical practice, mostly to be used in combinations.